Cluster Based Routing in NDN - Verma, Gaurav; Nandewal, Arun; Chandrasekaran, K. (ITNG 2015 : proceedings : 12th International Conference on Information Technology: New Generations : 13-15 April 2015, Las Vegas, Nevada, 2015)
Named Data Networking (NDN) being a potential future technology designed as a distribution network alternative to the present day host oriented IP-based host-oriented Internet architecture. Some arguments against NDN implementation over other candidate architectures are as mentioned. (1) Availability of extensive content which needs to be comprehended in accordance with its relevance and type. (2) Scalability and maintenance of burgeon networks on the subject of considering each bridging device as an independent node. This paper proposes a reliable and scalable ad-hoc routing protocol for NDN wireless networks. Functionality of protocol requires initial associating of each node with virtual coordinates and then distributing them among clusters or cliques. We focus on reducing the searching space for the route reliant to the number of nodes. Proposed protocol feasibility has been instituted with theorem and resulting graphs. This work proposes the idea of a protocol positioned to reduce the searching space and endure node failure within a network. As padding to the protocol perks consideration to reduce numbers of routers and caching the content packets are also considered.